Growing up shared : how parents can share smarter on social media-and what you can do to keep your family safe in a no-privacy world - Steinberg, Stacey (Sourcebooks, 2020)
"Is it okay to share details about my child's life on social media? What kinds of pictures should I avoid posting? Am I taking away their ownership of their future online footprint? In today's age of "sharenting," many parents are trying to strike the right balance between engaging with online communities they value and respecting their child's right to privacy and safety. Stacey Steinberg's investigation of the benefits and risks of sharing our kids' lives on social media will help any parent find the right path for their family to follow in the online world"--